2020
DOI: 10.1002/jnm.2825
|View full text |Cite
|
Sign up to set email alerts
|

A novel dual memristor hyperchaotic system and its application for secure communication based on three‐fold function projection synchronization

Abstract: A novel simplest four‐dimensional hyperchaotic system with dual memristors is designed by using a charge‐controlled memristor and a generalized voltage‐controlled memristor. Based on the conventional dynamic analysis method and MATLAB simulation software, the dynamic characteristics of the dual memristor hyperchaotic system such as Lyapunov exponent spectrum, phase diagram, and bifurcation diagram are studied. The novel system is found to exhibit singular nonlinear phenomena, such as limit cycle, state transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Balamurali Ramakrishnan et al (Ramakrishna et al, 2020) propose a nonlinear chaotic oscillator in a memristor-Josephson junction combination and discussed its synchronization characteristics. An et al (An et al, 2020) designed a dual memristor hyperchaotic system and synchronized it with three groups of drive response systems.…”
Section: Introductionmentioning
confidence: 99%
“…Balamurali Ramakrishnan et al (Ramakrishna et al, 2020) propose a nonlinear chaotic oscillator in a memristor-Josephson junction combination and discussed its synchronization characteristics. An et al (An et al, 2020) designed a dual memristor hyperchaotic system and synchronized it with three groups of drive response systems.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al (2020) discussed a secure communication application using a new hyperchaotic system with a stable equilibrium [2]. designed a new simple hyperchaotic system with dual memristors and applied it for a secure communication system [3]. Using a hyperchaotic Lorenz system, Ouannas et al (2021) suggested a new secure communication system, which is obtained by combining chaotic modulation, recursive encryption and chaotic masking [4].…”
Section: Introductionmentioning
confidence: 99%